Pengaruh Brand Image dan Word Of Mouth Terhadap Keputusan Pembelian di Kedai Kopi Maning Bekasi - Roselina Vindy Pramita; Herwin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
this research aims to show the influence of Brand Image and Word Of Mouth in Kopi Maning Bekasi Coffee Shop purchase decisions . There are three variables in this research including Brand Image, Word Of Mouth, and purchase decisions. The researchist used quantitative methods and the sample used in this research amounted 144 respondents who had bought at Kopi Maning Coffee Shop. . The technique used in this research is purposive sampling which is part of non-probability sampling. The research data is analyzed with SPSS 25 shows that Brand Image have an influence on Purchase Decisions, Word Of Mouth have an influence on Purchase Decisions, and together Brand Image and Word Of Mouth have influence on Purchase Decision.